Character association study in maize hybrids developed through integration of rapid cycle genomic selection and doubled haploid technology for heat stress tolerance - Swamy, N.; Kuchanur, Prakash H.; Patil, Ayyanagouda; Zaidi, Pervez H.; Vinayan, M. T.; Arunkumar, B.; Sowmya, H. C.; Dhanoji, M. M. (Sciencedomain International, 2023)
Heat stress is becoming a major constraint for maize production; therefore heat stress resilience has emerged as an important aspect in maize hybrids targeted for post rainy spring season. Selection of genotypes based on high grain yield under heat stress condition is often misleading and the identification of secondary traits also associated with grain yield may help in development of heat tolerant cultivars. Hence, the present research work to study the association of traits was conducted during summer and kharif 2018 and rabi 2018-19 at Bheemarayanagudi and Raichur using 111 testcross progenies of doubled haploids derived from C1, C2 and C3 cycles of multi-parental synthetic population 1 and 2 improved through rapid cycle genomic selection for heat stress tolerance. The phenotypic correlation analysis under heat stress and optimal conditions, number of kernels per cob and cob girth exhibited the strong positive association with grain yield per plant. Further, under early spring condition number of kernels per cob, cob length, cob girth and 100 grain weight recorded the strong positive association with grain yield per plant. However, when considering across heat stress, early spring and optimal conditions, the grain yield per plant showed positive and significant strong to moderate association with the traits viz., number of kernels per cob, cob length and cob girth under all the seasons. In addition, days to 50% silking showed significant negative correlation with grain yield per plant under heat stress and optimal condition. Hence, the simultaneous selection criteria for the genotypes that exerts early silking, higher number of kernels per cob, higher cob girth and lengthy cob should be the priority of breeders to achieve higher grain yields in maize under heat stress condition as well as optimal conditions.